RESIN COMPOSITION FOR GEL HIGH POLYMER SOLID ELECTROLYTE AND THE GEL HIGH POLYMER SOLID ELECTROLYTE - OKUMURA SOUBUN; AMANOKURA HITOSHI; SONOBE HIROYUKI; NISHIMURA SHIN; TABUCHI MASAHITO; MIURA KATSUTO (2002)
PROBLEM TO BE SOLVED: To provide a gel high polymer solid electrolyte, having both superior ion conductivity and mechanical strength, and which is applicable to various electrochemical devices. SOLUTION: This gel high polymer solid electrolyte contains (A) a polyether copolymer having an ethylene oxide denaturalized glycidyl ether compound and an ethylene oxide as main ingredients, and (B) a polymer of a fluorine compound, as an essential condition, and as necessary, (C) it will also contains a polyether polymer obtained from a composition for a gel high polymer solid electrolyte, in which a polymerizable compound having one or more ethylene unsaturated bonds in an element, and (D) an electrolyte.